Digital Capitalism and Coal Mine Workers - Akın Bakioğlu (tripleC: Communication, Capitalism & Critique)
One hundred and seventy-five years ago, in his book titled The Condition of the Working Class in England, Engels wrote about the ways in which the mine workers were exploited within the capitalist system. Classical economists believed that with the improvements in technology, capitalism would create egalitarian employment opportunities for everyone. In their opinion, the coal which served as a catalyser for the classical modernization had no place in the age of digital technology. However nowadays, especially in various developing countries such as Turkey, in the production of coal mines, the existing working conditions are the same as the ones that were applicable one hundred and seventy years ago and the exploitation of the labour of the workers continues. Notwithstanding, digital technologies serve for the control of capitalist production instead of the wellbeing of the workers. Coal has always had an important role in the historical continuity and discontinuity periods of capitalism. Considering the unbreakable link between the exploitation of nature and capitalist accumulation of capital, giving up coal and switching to renewable energy sources does not seem possible. The dialectical link between technology consumption and technology production is also one of the most important reasons for coal production to continue. This article argues that in Turkey today, the technology used in coal mine craft prioritises the control of labour rather than prioritizing the working comfort of the mine workers.